If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1k = 0 Solving 2 + -1k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1k = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1k = 0 + -2 -1k = 0 + -2 Combine like terms: 0 + -2 = -2 -1k = -2 Divide each side by '-1'. k = 2 Simplifying k = 2
| 2(x^2-5)(x^2-4x+5)=0 | | a^2+a+a^2=0 | | 36/3/5 | | 155.00x+7500.00=92440.00 | | X*2+5=-14 | | 39.55+0.20m=80 | | x^(2/3)-1 | | 15+3=18y | | 5b+3(4+5b)= | | x^2=7-2x | | 2x^7-16x^6+12x^5= | | 5+3(4+5)= | | (-15/2)(-1) | | 7x+1x=28+9x | | (324*80)= | | 2x^4-8x^3+40x-50=0 | | 7x+1x=14+9x | | 2.583+(-5.399)= | | 7x+1x=28+9 | | 3x/5-9=27 | | 2x-3=69-7x | | 4x^2=25x+21 | | 6(2w-1)=-30 | | 4(2x+4)+5(6x+7)= | | 1/x-4=12 | | 0.96=1.2 | | 7x+1x=14+9 | | 2x/5-9=27 | | 7x+1=4x+22 | | 3x^3-4x^2-25x+42=0 | | x=a+R-c | | 5x-3(x-11)=(2x-5)+2 |